The measurment of the ICT-competence in teacher training (Training and Practice : Journal of Educational Sciences, 2018)
The study intends to present the importance of ICT-competences and the possibilities of its development in teacher training. First, the concept and elements of teachers' ICT competences are clarified as well as factors related to the development of the area, including the role and significance of teacher training. Then, we will get an overview of previous ICT-focused research in teacher training. One of the common features of these is, that they mainly focus on access, activity and attitude but less on ICT competences. That is partly the reason for the significance of the research about ICT competences of teacher trainees detailed in the next part of the study. After presentation of the research design, its most important questions and measuring instruments, the first results of the pilot-research are presented, followed by discussing further research plans.